Faktor-Faktor yang Mempengaruhi Phlebitis pada Anak di RSUI Harapan Anda Kota Tegal - Dita Adelina, Dita Adelina; Nopi Nur Khasanah; Kurnia Wijayanti (STIKes Ibnu Sina Ajibarang, 2025)
Phlebitis is one of the most common complications that occur as a result of intravenous infusion, especially in pediatric patients. This condition is characterized by inflammation of the vein wall, which can cause pain, redness, and swelling around the puncture site. The high incidence of phlebitis in children requires serious attention because it can prolong hospitalization, increase healthcare costs, and reduce the overall quality of care. This study aimed to identify the factors associated with the occurrence of phlebitis in pediatric patients at RSUI Harapan Anda, Tegal City. This research employed a correlational analytic design with a cross-sectional approach. The sample consisted of 46 pediatric patients undergoing intravenous therapy in the inpatient ward, selected using purposive sampling. The research instrument was an observation sheet that included independent variables such as age, chronic illness, duration of infusion, infusion site, type of infusion fluid, and nurses’ skills. The dependent variable was the incidence of phlebitis. Data were analyzed using the chi-square test to determine the relationships between variables. The results showed that most patients were in the toddler age group (1–3 years), had chronic illnesses, underwent infusion for more than 72 hours, had high-risk puncture sites, used hypotonic fluids, and were treated by nurses with insufficient skills. Statistical analysis revealed significant associations between all independent variables and the occurrence of phlebitis. These findings highlight the importance of improving nurses’ competence through continuous training, strict monitoring of infusion duration and fluid type, as well as special attention to high-risk pediatric patients. Such efforts are expected to reduce the incidence of phlebitis and improve the quality of nursing care in hospitals.